A Single-Center Retrospective Study on the Initiation of Peritoneal Dialysis in Patients With Cardiorenal Syndrome and Subsequent Hospitalizations. (December 2020) - Auguste, Bourne L.; Agarwal, Arnav; Ibrahim, Ali Z.; Girsberger, Michael Y.; Abreu, Zita; McQuillan, Rory F.; Bargman, Joanne M.
Background: Inotropic dependence and diuretic resistance in patients with cardiorenal syndrome (CRS) lead to frequent hospitalizations and are associated with high mortality. Starting peritoneal dialysis (PD) acutely (within 2 weeks of a heart failure hospitalization) offers effective volume removal without hemodynamic compromise in this population. There is little data on this approach in the North American literature. Objective: To determine whether volume-overloaded patients with CRS on maximal doses of diuretic therapy had reduced hospitalization for heart failure following PD initiation. Design: Retrospective cohort study. Setting: Academic hospital network (University Health Network, Toronto, Ontario). Patients: Patients with CRS receiving a bedside catheter and starting PD within 2 weeks of insertion at the University Health Network from January 1, 2013, to December 31, 2018. Methods and measurements: Data for heart failure–related hospitalizations and length of stay 6 months before and after PD initiation were collected. Patients who died, switched to hemodialysis, or were transferred to another facility within 6 months of starting PD were excluded from the analysis. Results: We identified 31 patients with CRS who had a bedside PD catheter inserted. The average age of patients was 66.0 ± 13.0 years. There were 7 (22.6%) deaths and 4 (12.9%) transfers to other programs or hemodialysis within 6 months of catheter insertion. After exclusion, we analyzed hospitalization and length of stay data for 20 patients. The hospitalization rate 6 months before PD initiation was 6.9 admissions per 1000 patient-days. This decreased to 2.5 admissions per 1000 patient-days after PD initiation. In addition, there was also a significant reduction in the average length of stay per hospitalization (24.1-3.9 days; P = .001). Limitations: Our study did not assess the severity of heart failure symptoms using a standardized functional classification system. We did not assess quality of life and illness intrusiveness scores before and after starting dialysis, nor did we capture non–heart-failure-related hospitalizations or external admissions at other hospital sites. We limited eligibility to clinically stable patients with no prior major abdominal surgical history in a single Canadian PD program using bedside ultrasound approach for catheter insertions by experienced nephrologists and included a small number of patients. Conclusions: Volume-overloaded patients with CRS receiving maximal diuretic therapy have lower hospitalization rates and shorter stays after initiation of PD. The development of a bedside PD catheter insertion program and close collaboration between nephrology and cardiology services may facilitate acute start dialysis in this population.